The Role of Streptococcus spp. in Bovine Mastitis - Tina Kabelitz; Etienne Aubry; Kira van Vorst; Thomas Amon; Marcus Fulde (Microorganisms, 2021)
The Streptococcus genus belongs to one of the major pathogen groups inducing bovine mastitis. In the dairy industry, mastitis is the most common and costly disease. It not only negatively impacts economic profit due to milk losses and therapy costs, but it is an important animal health and welfare issue as well. This review describes a classification, reservoirs, and frequencies of the most relevant Streptococcus species inducing bovine mastitis (S. agalactiae, S. dysgalactiae and S. uberis). Host and environmental factors influencing mastitis susceptibility and infection rates will be discussed, because it has been indicated that Streptococcus herd prevalence is much higher than mastitis rates. After infection, we report the sequence of cow immune reactions and differences in virulence factors of the main Streptococcus species. Different mastitis detection techniques together with possible conventional and alternative therapies are described. The standard approach treating streptococcal mastitis is the application of ß-lactam antibiotics. In streptococci, increased antimicrobial resistance rates were identified against enrofloxacin, tetracycline, and erythromycin. At the end, control and prevention measures will be considered, including vaccination, hygiene plan, and further interventions. It is the aim of this review to estimate the contribution and to provide detailed knowledge about the role of the Streptococcus genus in bovine mastitis.